With a little help: Young women farmers’ experiences in India - Srinivasan, Sharada; Narayanan, Sudha (Practical Action Publishing Ltd, 2025)
We present four case studies of young women farmers in India, two each from Tamil Nadu and Madhya Pradesh. As outlined in the previous chapter, the case studies offer an in-depth view into how young women become farmers, their experiences as farmers and the challenges they face. They highlight similarities but also differences across the respondents. The concluding section draws implications from the four case studies to reflect on experiences of other young women farmers in this study but also what they illustrate of young women farmers’ experiences more broadly.